SOME METHODS FOR CALCULATING LOSSES OF FIXED SPRINKLER IRRATION UNDER THE INFLUENCE OF OPERATION PRESSURE AND SPRAYERS’ ARRANGEMENT - & Yacoub, Al-Mehmdy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was conducted in Al-Furat village-Heet district-Al-Anbar governorate-Iraq, in fall season-2017 aimed to evaluate some calculating methods of sprinkler irrigation losses calculated according to each of catch, athelen, and electrical conductivity methods. The experiment included two factors, first; operational pressure (P) with three levels; 250(p1), 300(p2), and 350(p3) kPa, while the second factor; sprayer arrangement (A) with two arrangements; rectangular (A1) with a space (24*18) m and square (A2) with a space (18*18) m. The results showed that the operational pressure 250 KPa with rectangular arrangement gave the highest percentage of sprinkler irrigation losses; 27.55%, 23.89%, and 8.20% for the catch, athelen, electrical conductivity methods, respectively. While the operational pressure 350 kPa with square arrangement gave the lowest percentage of the losses; 2.64%, 2.85%, and 9.36% for the catch, athelen and electrical conductivity methods, respectively. Therefore, the reduction of sprinkler evaporation losses depending on the used methods has provided quantities of water to be used to irrigate other areas of the unused land, added to the farmland, in order to achieve the food security that is proportional with the increasing population growth.